PENGARUH LINGKUNGAN TOKO TERHADAP KEADAAN EMOSIONAL DAN PERILAKU PEMBELIAN IMPULSIF KONSUMEN PENGUJIAN MODEL MEHRABIAN-RUSSELL - Febrina Annisa Fauziyah; Indah Fatmawati (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2017)
This study aims to analyze the influence of store environment on impulse buying behavior with emotional states as intervening variable using Mehrabian-Russell’s model. The store environment variables in this study include time availability, atmospheric factors, presence of others, and perceived crowdness. Using Mehrabian-Russell’s model, it is hypothesized that emotional state mediates the effects of store environment variables on impulse buying behavior as a dependent variable. The object in this study is Matahari Department Store in Yogyakarta. Sample of 166 respondents were selected by using purposive sampling method. Data were collected by using field survey technique. Normality, validity and reliability tests were conducted to test the quality of research instruments. The data analysis was conducted by using multiple linear regressions to test the research hypothesis. Results showed that atmospheric factors. as predicted, positively affect the emotional states. While perceived crowdness, consistent to the hypothesis, negatively affect the emotional states. The emotional states also positively affects the impulse buying behavior. The hypothesis of time availability and presence of others were not supported in this research. The findings of this research indicate that creating a proper atmospheric factors and creating a convenience store lay out to avoid crowdness are essential to stimulate impulse buying behavior.